Association between functional status at hospital discharge and long-term survival after out-of-hospital-cardiac-arrest. (July 2021) - Chocron, Richard; Fahrenbruch, Carol; Yin, Lihua; Guan, Sally; Drucker, Christopher; Shin, Jenny; Eisenberg, Mickey; Chatterjee, Neal A.; Kudenchuk, Peter J.; Rea, Thomas
Abstract: Background: Out-of-hospital cardiac arrest (OHCA) causes brain injury. Functional status of survivors at hospital discharge is a core resuscitation measure, frequently using the Cerebral Performance Category (CPC) or modified Rankin Scale (mRS). Which scale better predicts long-term survival following OHCA is not known. Methods: We evaluated long-term survival after hospital discharge in a retrospective cohort of persons resuscitated from OHCA in King County, WA from 2007 to 2015. Patients were independently assessed at discharge using both scales, leveraging the regional quality improvement registry, which records the 5-level CPC, and concurrent research studies involving the Resuscitation Outcomes Consortium, which used the 7-level mRS, taken from information in the hospital record. The risk of mortality associated with CPC and mRS categories was estimated using Kaplan–Meier survival analysis and Cox proportional hazards regression. Results: Among 878 eligible patients discharged alive, there were 358 deaths during 9118.5 person-years of follow-up. Overall 1, 5 and 10-year survival was 84.4%, 68.5%, and 53.7% and varied according to CPC and mRS (p < 0.01 per Kaplan–Meier). Compared to CPC-1, hazard ratio (HR) increased incrementally for CPC-2 = 1.33 (1.03–1.73), CPC-3 = 1.90 (1.37–2.65), and CPC-4 = 8.25 (5.63–12.10). Compared to mRS = 0, HR for mRS-1 = 1.02 (0.66–1.58), mRS-2 = 1.52 (1.00–2.32), mRS-3 = 1.41 (0.92–2.14), mRS-4 = 2.00 (1.37–2.97), and mRS-5 = 4.90 (3.23–7.44). Conclusion: In OHCA survivors, CPC and mRS scales both predicted long-term survival. However mRS 0−1 and 2−3 groups did not have distinct prognoses, suggesting that a consolidated mRS score may simplify capture of relevant prognostic information for survival predictions.